2003
DOI: 10.1007/s00436-003-0847-0
|View full text |Cite
|
Sign up to set email alerts
|

Ion regulation in the different life stages of Trypanosoma cruzi

Abstract: Different ion and pH regulation mechanisms have been detected in the three main life stages of Trypanosoma cruzi: epimastigote, metacyclic trypomastigote and amastigote. Treatment with amiloride showed that the Na(+)/H(+) exchanger participated in all three forms. The Na(+)/K(+) ATPase exchanger appeared to be more active in the epimastigote than in the other forms. V-H(+)-ATPase inhibitors revealed the activity of this regulatory mechanism in the amastigote and epimastigote forms, while treatment with oligomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Similar results were previously obtained for other T. cruzi amino acid transporters, such as arginine and proline, where the maximum transport activities were determined in the 4 to 5 pH range [6,8]. Parasites are exposed to variations in the extracellular pH during its life cycle, for example within the digestive tract of the insect vector (pH 5–9) [2,24], mammalian blood (neutral pH), mammalian intracellular parasitophorous vacules (pH 4.5–5.5) [24] and cytoplasm (neutral pH). Therefore, an increase in the transport of arginine, proline and aspartate should be expected in a more acidic environment present in the insect and in the mammalian hosts.…”
Section: Discussionmentioning
confidence: 87%
“…Similar results were previously obtained for other T. cruzi amino acid transporters, such as arginine and proline, where the maximum transport activities were determined in the 4 to 5 pH range [6,8]. Parasites are exposed to variations in the extracellular pH during its life cycle, for example within the digestive tract of the insect vector (pH 5–9) [2,24], mammalian blood (neutral pH), mammalian intracellular parasitophorous vacules (pH 4.5–5.5) [24] and cytoplasm (neutral pH). Therefore, an increase in the transport of arginine, proline and aspartate should be expected in a more acidic environment present in the insect and in the mammalian hosts.…”
Section: Discussionmentioning
confidence: 87%
“…The rate of proton extrusion was moderately decreased in absence of K + , but practically abolished in absence of Na + arguing about the presence of Na + /H + and K + /H + exchangers. Biochemical evidences support the presence of these transporters in T. cruzi (Van Der Heyden and Docampo, 2002;Gil et al, 2003), and at least 1 gene encoding for a putative Na + /H + antiporter (TcCLB.510511.9) is present in the T. cruzi genome, but no expression or functional evidences have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the maintenance of intracellular ion homeostasis is crucial for protozoa survival, because ion homeostasis plays an important role in maintaining membrane potential and cytosolic enzymes activities . Studies found that some protozoa, for example, Trypanosoma cruzi, have complex ion regulation systems, including Na + /H + exchanger, H + ‐ATPase and HCO3/Cl ‐ exchanger, to adapt to different environment, so that the cells can survive under adverse conditions. However, high concentration of inorganic ions would exert detrimental effect on microorganisms, such as protozoa, microalgae and yeast, and plant as well.…”
Section: Resultsmentioning
confidence: 99%